Explore BrainMass

Recurrence Relations.

This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

Find the solution to
an = 2an-1 + an-2 -2an-3
for n= 3,4,5,..., with a0 = 3, a1=6, and a2=0.

Find the solution to
an= 5an-2 - 4an-4
with a0 = 3, a1 = 2, a2 = 6, and a3 = 8.

(I have attached the full problem below.)

© BrainMass Inc. brainmass.com March 22, 2019, 12:57 am ad1c9bdddf


Solution Preview

Hello and thank you for posting your question to Brainmass.
The solution is attached ...

Solution Summary

This solution provides steps to solve the recurrence relations problems.